Al-‘Ulamā’ wa al-Ḥukūmaa wa al-Mujtami ‘a fi Indonesiā al-Mu’āṣiraa: Dirāsaa Tahdhībi al- li majlisi al-‘Ulamā’ al-Indonesiyyī - M. Atho Mudzhar (Al-Jami'ah: Journal of Islamic Studies, 1996)
This article tries to analyze the relation between the MUl (Majelis Ulama Indonesia, or Council of Indonesian Ulama), the government, and the Muslim Community in last six-seven years. This study begins with an extensive and deep research previously conducted by the writer in preparation for writing his dissertation to be submitted to UCLA. The main focus of the writer’s research at that time was the role and development of the MUl between 1975-1983. ln his previous research, the writer described four significant roles played by the MUI in the Indonesian Muslim community First. the MUI played an important role in preserving and developing good relations with various Islamic organizations. At the beginning, many Muslim leaders were suspicious of the presence of the MUI and therefore they rejected the establishment of the MUI on the grounds that it would be used as a political tool by the government. To convince Muslim figures that the MUI was not the government’s political tool, it made various efforts such as inviting them to observe and participate in its activities or inviting them to discuss and solve the Muslim community's problems. In addition, the MUI showed is strong commitment to the Muslim community’s social concerns as well as its involvement in many national and international programs and activities. By doing so, the presence of the MUI was finally accepted by the whole Muslim community. second, the MUI aimed at establishing good relations with the government. The MUI's relations with the Muslims and the government were complex in nature. on one hand, many Muslim figures at the beginning were nor interested in the formation of the MUI because they regarded it as a government’s tool to legitimize its policies towards the Muslims. On the other hand, the government itself financially supported the MUI so that the relation between the two sides grew well. Between 1975-1988 the MUI produced twenty-two. fatwa’s (legal opinions): eight supported the government’s policies, eleven were neutral, and three were in contradiction to its policies However, generally speaking, the MUI's relation with the government became better and more cooperative in the face of religious and national affairs Third, the MUI encouraged the Muslims to take part very actively and extensively in the whole process of national development. These efforts were made by the MUI by cooperating with certain Ministries. Fourth. the MUI acted as a mediator which played a pivotal role in establishing good and harmonious relations between the Muslim community and other social-religious group existing in the country. In last six-seven years (from 1989-now). The MUl has persisted in keeping its significant role (as Mentioned above), even with more intensive and effective way. The MUI proves itself as an effective religious institution so that its presence and its function can be accepted and acknowledged by the Muslim as a whole. In this periode. The MUI intensifies its activities by implementing various program which had never been done before such as taking the of establishing the muamalat Bank and sending Muslim preachers (dā’ī’s) to the transmigration areas. More and More fatwā’s in this periode have also been produced by the MUI. This periode also witnesses a better and more cooperative relation between the MUI and the government. The MUI continues to motivate all segments of the Muslim community to be more involved in the whole process of social. educational, and cultural development carried out by the government. It also urges Muslim to support the government's political interests, especially in connection with its policies to preserve national unity Integrity and to maintain national security and dynamic stability in the country. [Tulisan ini mencoba mengkaji hakikat hubungan Majelis Ulama Indonesia (MUI), pemerintah dan masyarakat di Indonesia selama 6-7tahun terakhir. Analisis dalam kaiian ini berangkat dari hasil penelitian terdahulu penulisnya terhadap MUI periode 1975-1993. Dalam penelitian terdahulu itu ditemukan empat sikap pokok MUI yang mewadai kegiatanny: Pertama, adanya keinginan di pihak MUI untuk dapat diterima masyarahat dan untuk membangun hubungan baik dengan berbagai organisasi keislaman. Pada mulanya sebagian tokoh-tokoh umat Islam menolak kehadiran MUI karena dicurigai sebagai semata alat politik pemerintah belaka. Namun berkat kredibilitas para tokoh yang pernah menjadi ketua umumnya dan usaha-usaha yang dilakukannya, seperti mengunjungi organisasi-organisasi Isiam atau mengundang para pengurusnya untuk Menghadiri berbagai pertemuan MUI untuk membahas aneka persoalan, penunjukan komitmen yang tinggi terhadap kepentingan Islam dan kaum Muslimin serta kererlibatannya dalam berbagai kegiatan yang bertaraf internasional, akhinya ia lambat laun diterima oleh masyarakat Islam. Kedua, adanya keinginan untuk membina dan mempertahankan bubungan baik dengan pemerintah. Hubungan dengan pemerintah ini agak kompleks. Di satu sisi pada mulanya tokoh-tokoh Islam tidak tertarik kepada pembentukan MUI karena beberapa faktor politik sebelum terbentuknya MUI dan setelah terbentuknya karena adanya kesan pemerintah menekan MUI agar selalu melegitimasi kebijaksanaan-kebijaksanaannya. Di sisi lain pemerintah sendiri terus memberikan dukungan kepada MUI melalui bantuan finansial dan dari pihak MUI sendiri terdapat usaha-usaha untuk terus memperkokoh hubungan dengan pemerintah sehingga dari 22 fatwa yang diterbitkan selama periode 1975-1988 terdapat 8 farwa yang mendukung kebijaksanaan pemerinrah, 11 fatwa netral dan hanya tiga yang beroposisi terhadap pemerintah. Akan tetapi secara umum hubungannya dengan pemerintah bejalan ke arah semakin membaik. Ketiga, keinginan untuk mendorong umat Islam agar berpartisipasi sebanyak mungkin dalam pembangunan nasionaI. Ini dilakukan dengan menerbitkan keputusan-keputusan bersama dengan Departemen-Departemen tertentu. Keempat, keinginan untuk membina hubungan baik dengan kelompok-kelompok agama lain. Hubungan ini bersifat kompleks dan bahkan konflik dalam mana MUI memainkan Perannya dalam upaya untuk membina kerukunan antar pemeluk agama di mana umat Islam merupakan kelompok terbesar (88 %) yang karena itu, pada mulanya, enggan untuk duduk bersamal dengan kelompok agama lain yang lebih kecil. Pada periode 6 - 7 tahun terakhir ini (1989-hingga sekarang) MUI kerap mempertahankan empat sikap yang telah diambilnya pada periode terdahulu dengan perubahan dan intensitas dan aplikasi. Dalam periode ini MUI berhasil Mengukuhkan kehadirannya di tengah-tengah umat Islanm yang terbukti dari penerimaan penuh masyarakat dan organisasi  lslam terhadap keberadaannya. MUI Meningkatkan aktifitasnya dengen mencanangkan program-program khusus yang pada periode sebelumnya tidak dilakukan karena waktu itu ia lebih memfungsikan diri sebagai pemberi nasihat dan fatwa. Peningkatan aktifitas pada periode sesudah tahun 1990 terecermin dalam keterlibatannya, misalnya, mendirikan Bank Mu'amalat Indonesia, mengirim para da'I ke daerah transmigrasi, Menerbitkan sertifikat Makanan halal. Dalam kaitan hubungan baik dengan pemerintah, kedae pihak MUI dan pemerintah dapat membina kerja sama positif sebagai dampak dari dihilangkannya beberapa faktor pengganjal hubungan tersebut sebelumnya. Mengenai sikap MUI yang lahir dari keinginan untuk lebih mendorong umat Islam berpartisipasi lebih besar dalam pembangunan nasional sejalan dengan berkembangnya hubungan baik dengan pemerintah. MUI memberikan nasihat-nasihat yang berdimensi luas baik terhadap pemerintah maupun umat Islam berkenaan dengan masalah-masalah seperti ketahan dan stabilitas nasional pengumpulan zakat, pengembangan Pendidikan  dan sekolah-sekolah Islam dan lain-lain. Mengenai kerukunan umat beragama dikembangkan melalui Wadah Musyawarah Antar Umat Beragam, sekalipun sensitifitas terhadap Kristenisasi masih tetap muncul di permukaan.]